1995
DOI: 10.1002/cne.903630212
|View full text |Cite
|
Sign up to set email alerts
|

Localization of α7 nicotinic receptor subunit mRNA and α‐bungarotoxin binding sites in developing mouse somatosensory thalamocortical system

Abstract: Previous studies in rat, showing a transient pattern of expression of the alpha 7 nicotinic acetylcholine receptor in the ventrobasal thalamus and barrel cortex during the first 2 postnatal weeks, suggest that these receptors may play a role in development of the thalamocortical system. In the present study, in situ hybridization and radiolabeled ligand binding were employed to examine the spatiotemporal distribution of alpha 7 mRNA and alpha-bungarotoxin binding sites in the thalamocortical pathway of mouse d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 38 publications
5
40
0
Order By: Relevance
“…59 Finally, there is also evidence that ACh receptors are expressed in the embryonic thalamus. 13,60,61 Taken together with the results presented here, we suggest that ACh released from cortical cells and/or cholinergic cortical projections participates to the formation of thalamocortical projections by regulating growth cone pauses at decision regions of thalamic axons.…”
Section: Discussionsupporting
confidence: 79%
“…59 Finally, there is also evidence that ACh receptors are expressed in the embryonic thalamus. 13,60,61 Taken together with the results presented here, we suggest that ACh released from cortical cells and/or cholinergic cortical projections participates to the formation of thalamocortical projections by regulating growth cone pauses at decision regions of thalamic axons.…”
Section: Discussionsupporting
confidence: 79%
“…Although nicotinic receptors and serotonin 5-HT 3 receptors are expressed in the neocortex (Parkinson et al, 1988;Tecott et al, 1993;Weavers et al, 1994;Bina et al, 1995;Lobron et al, 1995;Nakayama et al, 1995), and widespread cholinergic and serotonergic innervations are found in the majority of cortical areas, no indication of fast transmission mediated by these transmitters has been reported previously. However, using single-cell patch-clamp recordings of spontaneous and evoked activity, we were able to demonstrate that both nicotinic acetylcholine and ionotropic serotonin receptors contribute to fast excitatory synaptic transmission in all layers of the developing ferret visual cortex.…”
Section: Discussionmentioning
confidence: 95%
“…These results imply an interesting species difference; however, it should be noted that the MLA dose used may block non-␣7 receptors, and the mecamylamine dose may preferentially block non-␣7 receptors (e.g., Raggenbass and Bertrand 2002). Also, the authors did not explicitly consider the rapid changes in nAChR expression that occur during the first three postnatal weeks in sensory cortex and thalamus (Fuchs 1989;Bina et al 1995;Broide et al 1995Broide et al , 1996. These changes are detailed below ("nAChRs and Sensory Cortex Development"), and it remains a possibility that different nAChR subtypes regulate thalamocortical transmission at different ages (e.g., Fig.…”
Section: Cellular Bases Of Nicotinic Regulation Of Sensory Cortexmentioning
confidence: 99%